The Bilbao Effect in Indonesia: Architectural Representation and the New Image of Banyuwangi City - Susilo Kusdiwanggo; Alya Lailatul Azizah (University of Merdeka Malang, 2026)
This study analyzes the role of architectural representation in the city branding strategy of Banyuwangi Regency, which has undergone a transformation from a mystical city to a cultural city. The objective of this study is to comprehend the process of spatial representation through public architectural design developed during the leadership of Regent Azwar Anas (2010–2021). Utilizing a qualitative narrative approach within a constructivist paradigm and deductive reasoning, this study examines five iconic architectural projects revitalized in Banyuwangi and conducts in-depth interviews with six architects and project managers. A thorough examination of the data, employing open coding, axial coding, and selective coding techniques, revealed that architecture was strategically employed as a medium for transforming the city's identity through three main narratives: the local Bilbao effect shaping visual appeal; the representation of Osing culture through symbolic elements in building design; and the transformation of public perception through the revitalization of public spaces. The discussion establishes a connection between these narratives and the theories of the circuit of culture and urban cultural terraforming, thereby asserting that architectural representation is not merely aesthetic but also political, social, and cultural. These findings contribute to our expanded understanding of city branding as a multidimensional process and generate opportunities for further study on community involvement and the role of spatial policies in the production of urban identity. Keywords: Banyuwangi; Bilbao effect; City branding; City identity; Cultural representation; Iconic architecture; Revitalization of public spaces.